An AfD Victory in Thuringia: A Deep Dive Into the 2024 state Election - Hananto, Ridwan Sri; Nugrahani, Henny Saptatia Drajati (International Journal of Integrative Sciences, 2025)
In the 2024 state election in Thuringia it was hence another final warning for Germany, with the Alternative for Germany (AfD) as overall winner. This article dives into the many contours of AfD's rise, including populism; anti-immigrant sentiment and larger societal disaffection. The AfD's rise, together with its accompanying challenges and opportunities for Thuringia if party divisions persist, these consider will have implications beyond the region for wider European politics are analyzed using a mixed-methods approach combining quantitative data analysis and qualitative insights from interviews and survey data on voter behavior and party dynamics. The results speak volumes of the nuances between today's electoral quagmire and the challenges posed by populist movements. Here, will be analysed how the AfD managed to win so many votes and offers a few suggestions on how we can tackle this rise of populism in Europe